Practice Feedback Interventions: 15 Suggestions for Optimizing Effectiveness - Brehaut, Jamie C; Colquhoun, Heather L; Eva, Kevin W; Carroll, Kelly; Sales, Anne; Michie, Susan; Ivers, Noah; Grimshaw, Jeremy M (Annals of internal medicine, 2016)
Electronic practice data are increasingly being used to provide feedback to encourage practice improvement. However, evidence suggests that despite decades of experience, the effects of such interventions vary greatly and are not improving over time. Guidance on providing more effective feedback does exist, but it is distributed across a wide range of disciplines and theoretical perspectives. Through expert interviews; systematic reviews; and experience with providing, evaluating, and receiving practice feedback, 15 suggestions that are believed to be associated with effective feedback interventions have been identified. These suggestions are intended to provide practical guidance to quality improvement professionals, information technology developers, educators, administrators, and practitioners who receive such interventions. Designing interventions with these suggestions in mind should improve their effect, and studying the mechanisms underlying these suggestions will advance a stagnant literature.